2012
DOI: 10.1093/humrep/des013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryopreservation and transplantation on the expression of kit ligand and anti-Mullerian hormone in human ovarian tissue

Abstract: Grafting and/or gonadotrophin stimulation appear to affect the follicular expression of KL, which may alter oocyte quality. AMH expression in growing follicles after ovarian tissue transplantation may be one of the factors contributing to the preservation of resting follicles in 28-week-old grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 41 publications
5
31
0
Order By: Relevance
“…2f and 3), demonstrating that follicles are functional after long-term autografting. These data are consistent with previous results showing ungrafted fresh tissue to contain around 60 % of follicles positive for AMH, increasing to around 80 % after slow-freezing of human ovarian tissue grafted to mice [40].…”
Section: Discussionsupporting
confidence: 93%
“…2f and 3), demonstrating that follicles are functional after long-term autografting. These data are consistent with previous results showing ungrafted fresh tissue to contain around 60 % of follicles positive for AMH, increasing to around 80 % after slow-freezing of human ovarian tissue grafted to mice [40].…”
Section: Discussionsupporting
confidence: 93%
“…It is also important to recognize that many studies report the effects of vitrification shortly, if not immediately, after thawing the cryopreserved tissue. While there is overwhelming evidence that grafting ovarian tissue following warming leads to activation of the primordial follicle reserve due to ischemiareperfusion [30,35,36], there is contradictory evidence as to whether cryoprotectant exposure and/or vitrification of ovarian tissue induces activation of primordial follicles. One study found that the type of cryoprotectant used affects the results, with propanediol increasing the activation rate following grafting more than with DMSO [37].…”
Section: Discussionmentioning
confidence: 99%
“…45 The number of primordial follicles that enter the growing pool is not likely to be influenced by the high levels of FSH for the 14 days after transplantation as receptors for this ligand are not present. 27 Local peptide hormones such as Kit Ligand or anti-Mullerian hormone have also been implicated in follicle activation after transplantation 46 and could be supplemented through peptide delivery from the biomaterial. Moreover, systems biology analysis of follicles across various stages of development are identifying key factors.…”
Section: Fig 6 Graft Function (A)mentioning
confidence: 99%